Impact of Earthquake Magnitude on Lives lost during Shock - Gaya, Ibrahim Faruk; Adamu Bara, Aminu; Abdullahi, Ahmad; Audu Zanuwa, Mu'azu; Adamu Muhammad , Kamaludeen; Umar Idris, Shehu (Research Centre of Inorganic Materials and Complexs, 2021)
Abstract Earthquake is one of the catastrophic natural disasters in the history of mankind which consumed hundreds and thousands of human lives every year. Attitude of man in handling natural environment make earthquakes inevitable. The study was design to examine the impact of earthquake magnitude on lives loss during earthquakes. Data adopted for study are solely secondary data which include; journals, textbooks, published and unpublished document. Sampled was derived using purposive sampling techniques, earthquakes that lives were loss during their occurrence characterized with 6.0Mw and above were selected as sample. Regression analysis, maps QGIS software, tables and graphs were used for data analysis in study. The result of the research indicate a fair relation among studied variables. Fig.1.1 Multiple R=0.073, fig. multiple=0.454 and fig. multiple R=0.452. Multiple R determine the nature of relation between study variables, the close the value of multiple R is to 1 the strong the relationship. Which means fair relationship exist between earthquake magnitudes and live loss during 1990-2019 earthquakes. And R2 result fig. 1.1, 1% of the lives lost during earthquakes 1990-1999 are determine by earthquake magnitude, R2 result in fig. 1.4 indicated 21% of the lives lost during earthquakes 2000-2009 are determine by earthquake magnitude and R2 result in fig.1.6 demonstrate 20% of the lives loss during earthquakes 2010-2019 are determine by earthquake magnitudes. Significant F results are fig. 1.1 significant F =0.613, fig. 1.4 significant F=0.001 and fig. 1.6 significant F=0.0004. Two out of the three significant F result indicated that the result of the research is reliable while one result indicated that the result is less reliable.